Fate of nickel in soybean seeds dressed with different forms of nickel - Bezerra de Oliveira, Jessica; Rodrigues Marques, João Paulo; Rodak, Bruna Wurr; Galindo, Fernando Shintate; Carr, Natalia Fernandes; Almeida, Eduardo; Araki, Koiti; Gonçalves, Josué Martins; Rodrigues dos Reis, André [UNESP]; van der Ent, Antony; Pereira de Carvalho, Hudson Wallace; Lavres, Jose (Elsevier, 2022)
The pathways whereby nickel (Ni) moves within seeds after fertilization of different Ni-seed dressings in soybean seed remains unclear. This study aimed to evaluate the effect of Ni sources, i.e., different size particles, on germination rate of soybean seeds, and uptake/translocation of Ni by roots and seeds in soybean. For this, seeds were treated with macrometric Ni-sulfate (hereafter called Macro-NiSO4), micrometric Ni-hydroxide (Micro-Ni(OH)2), nanometric Ni-hydroxide (Nano-Ni(OH)2) particles, and negative control without Ni application; evaluated by X-ray fluorescence (μ-XRF), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDS) analysis. The results show that seeds treated with Nano-Ni(OH)2 had wider Ni distribution in the seeds and into the radicle, while the treatment with Micro-Ni(OH)2 particles resulted in Ni diffused around the seeds. Regardless of the Ni-source type, the coated seeds had hotspots of high Ni in the hilum, but no transfer of Ni into the cotyledons. The application of Macro-NiSO4 and Micro-Ni(OH)2 particle had a positive impact on early seedling development increasing germination rate, root length and Ni distribution in the tissues. These results bring to light that in all treatments, Ni remained attached to the seed coat (especially the hilum) and did not move towards the emerging cotyledons, being transferred to the rhizosphere soil afterwards, and finally was taken up by the radicle, or seedling primary roots. However, further studies are necessary to define the proper Nano-Ni(OH)2 rate on soybean seeds avoiding excessive Ni uptake and impaired initial root development.
Keywords: Glycine max [L.] merril; Nanoparticles; Seed treatment; Soil rhizosphere; X-ray diffractometry; X-ray fluorescence